MONITORING PERUBAHAN GARIS PANTAI DENGAN CITRA SATELIT DI MUARA GEMBONG BEKASI - Hermansyah Putra; Lilik Budi Prasetyo; Nyoto Santoso (Graduate School Bogor Agricultural University (SPs IPB), 2016)
This study discussed themonitoring of coastline changesaccording to accretion and abrasion. The aim this study is to calculate the shoreline change within the last 10 years in Muara Gembong, Bekasi. This research using remote sensing approach and data from Landsat Satellite Imagery. The results indicate a change in the form of accretion and erosion on the shoreline. The abrasion average are 230.89 to 34.95 m/yr or 202 589 to 15,911 m2/yr. While the accretion average are 34 to 172.39 m/yr or 7044 to 47 205 m2/yr. This study concluded that accretion and abrasion of coastline,caused mainly byland conversion to enhance coast area made by a resident to fishfond, rice field and settlements, as well as sedimentation.